59.5k views
2 votes
Ill give 5 star i need help

A transformation T: (x, y) (x - 5, y + 3).

The image of A(2, -1) is

(3, 2)
(-3, -2)
(-3, 2)

User Madfriend
by
5.9k points

1 Answer

3 votes

Given:

Transformation is


T:(x,y)\to (x-5,y+3)

To find:

The image of A(2,-1).

Solution:

The rule of transformation is


(x,y)\to (x-5,y+3)

To find the image of A(2,-1). Put x=2 and y=-1 in the above rule of transformation.


A(2,-1)\to A'(2-5,-1+3)


A(2,-1)\to A'(-3,2)

Therefore, the image of A(2,-1) is A'(-3,2).

User WarrenB
by
6.5k points